Neuromuscular Versus Quadriceps Strengthening Exercise in Patients With Medial Knee Osteoarthritis and Varus Malalignment: A Randomized Controlled Trial1. Issue 4 (April 2014) - Bennell, Kim L.; Kyriakides, Mary; Metcalf, Ben; Egerton, Thorlene; Wrigley, Tim V.; Hodges, Paul W.; Hunt, Michael A.; Roos, Ewa M.; Forbes, Andrew; Ageberg, Eva; Hinman, Rana S.
<x xml:space="preserve">Abstract</x> Objective To compare the effects of neuromuscular exercise (NEXA) and quadriceps strengthening (QS) on the knee adduction moment (an indicator of mediolateral distribution of knee load), pain, and physical function in patients with medial knee joint osteoarthritis (OA) and varus malalignment. Methods One hundred patients with medial knee pain, mostly moderate‐to‐severe radiographic medial knee OA, and varus malalignment were randomly allocated to one of two 12‐week exercise programs. Each program involved 14 individually supervised exercise sessions with a physiotherapist plus a home exercise component. Primary outcomes were peak external knee adduction moment (3‐dimensional gait analysis), pain (visual analog scale), and self‐reported physical function (Western Ontario and McMaster Universities Osteoarthritis Index). Results Eighty‐two patients (38 [76%] of 50 in the NEXA group and 44 [88%] of 50 in the QS group) completed the trial. There was no significant between‐group difference in the change in the peak knee adduction moment (mean difference 0.13 Nm/[body weight × height]% [95% confidence interval (95% CI) −0.08, 0.33]), pain (mean difference 2.4 mm [95% CI −6.0, 10.8]), or physical function (mean difference −0.8 units [95% CI −4.0, 2.4]). Neither group showed a change in knee moments following exercise, whereas both groups showed similar significant reductions in pain and improvement in physical function. Conclusion Although comparable improvements in clinical outcomes were observed with both neuromuscular and quadriceps strengthening exercise in patients with moderate varus malalignment and mostly moderate‐to‐severe medial knee OA, these forms of exercise did not affect the knee adduction moment, a key predictor of structural disease progression.